Efficacy of therapeutic exercise for temporomandibular disorders as assessed by magnetic resonance imaging: a case report - Yamaguchi, Yoshihiro (J Phys Ther Sci, 2020)
[Purpose] The efficacy of exercise therapy in temporomandibular disorders has been recognized. Here, we present our experience with exercise therapy. [Participant and Methods] A 25-year-old female with a sudden onset of mouth opening limitation in October 2018 was admitted to our hospital in November 2018. Based on our initial findings, the patient was diagnosed with left disc derangement of the temporomandibular joint without reduction. A definitive diagnosis was established following magnetic resonance imaging in December 2018. Subsequently, range-of-motion exercises for the temporomandibular joint as passive movements and self-traction therapy as active movements were conducted. Magnetic resonance imaging was repeated 4 months after the first treatment. [Results] The temporomandibular joint disc remained in anterior dislocation during mouth opening and closing. The mouth opening joint motion was significantly improved compared to the pre-therapy range. The pain-related visual analog scale score also significantly improved. [Conclusion] The range of motion of the temporomandibular joint was improved by range-of-motion exercises for the temporomandibular joint, and was maintained and managed using self-traction therapy. Improvement of the range of motion was confirmed by magnetic resonance imaging.